Determination of Typology Characteristics of Consumers Based on Behavioral Characteristics of Older Women - Kodirova D.Kh; Nigmatova F. U; Nematova L.Kh (Zien Journals, 2022)
In the article , the implementation of social behavior practices by older people depends on the processes and phenomena taking place in society, the activities of social institutions and organizations, the characteristics of the interaction of the individual with the social environment, the value orientations of the individual, the traditions accepted in society, norms and rules, the individual characteristics of a person and etc., regulating the life of people.
Keywords: individual; elderly people; mips; physiques